Varied Outcomes of Prolonged Delirium Tremens – A Case Series - Poulomi Ghosh; Sudip Mukherjee; Alicia Perti; Dhrithi Mushthi; Suprakash Chaudhury; Shubham Kulkarni (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Alcohol use disorder, that is, the prolonged use and abuse of alcohol, is attributed to be one of the most common conditions to pose a high burden of disease, causing various behavioral, physical, and psychological impairments, and is the eighth leading risk factor for global mortality. After a period of heavy alcohol consumption, abruptly stopping it can lead to alcohol withdrawal. Alcohol withdrawal in severe cases can lead to delirium tremens (DT). It typically begins between the third and fifth day after quitting drinking and lasts for up to 24 hours to 6 days. It is rare to see DT lasting more than 10 days, known as protracted DT. Here, we present a series of cases having prolonged DT with complicated outcomes and results.